Chromatin Changes at the PPAR-γ2 Promoter During Bone Marrow-Derived Multipotent Stromal Cell Culture Correlate With Loss of Gene Activation Potential. (26th May 2015) - Lynch, Patrick J.; Thompson, Elaine E.; McGinnis, Kathleen; Rovira Gonzalez, Yazmin I.; Lo Surdo, Jessica; Bauer, Steven R.; Hursh, Deborah A.
Abstract: Bone marrow-derived multipotent stromal cells (BM-MSCs) display a broad range of therapeutically valuable properties, including the capacity to form skeletal tissues and dampen immune system responses. However, to use BM-MSCs in a clinical setting, amplification is required, which may introduce epigenetic changes that affect biological properties. Here we used chromatin immunoprecipitation to compare post-translationally modified histones at a subset of gene promoters associated with developmental and environmental plasticity in BM-MSCs from multiple donors following culture expansion. At many locations, we observed localization of both transcriptionally permissive (H3K4me3) and repressive (H3K27me3) histone modifications. These chromatin signatures were consistent among BM-MSCs from multiple donors. Since promoter activity depends on the relative levels of H3K4me3 and H3K27me3, we examined the ratio of H3K4me3 to H3K27me3 (K4/K27) at promoters during culture expansion. The H3K4me3 to H3K27me3 ratios were maintained at most assayed promoters over time. The exception was the adipose-tissue specific promoter for the PPAR-γ2 isoform of PPAR- γ, which is a critical positive regulator of adipogenesis. At PPAR-γ2, we observed a change in K4/K27 levels favoring the repressed chromatin state during culture. This change correlated with diminished promoter activity in late passage cells exposed to adipogenic stimuli. In contrast to BM-MSCs and osteoblasts, lineage-restricted preadipocytes exhibited levels of H3K4me3 and H3K27me3 that favored the permissive chromatin state at PPAR- γ2. These results demonstrate that locus-specific changes in H3K4me3 and H3K27me3 levels can occur during BM-MSC culture that may affect their properties. Stem Cells 2015;33:2169–2181